Global, regional, and national burden of chronic respiratory diseases and associated risk factors, 1990–2019: Results from the Global Burden of Disease Study 2019 - Chen, Xiang; Zhou, Cheng-Wei; Fu, Yang-Yang; Li, Yao-Zhe; Chen, Lei; Zhang, Qing-Wei; Chen, Yan-Fan (Frontiers in Medicine, 2023)
Background The burden of chronic respiratory diseases has changed over three decades. To describe the spatiotemporal trends of prevalence, mortality and disability adjusted life years (DALY) due to chronic respiratory diseases(CRDs), across the globe during 1990-2019 using data from the Global Burden of Disease Study 2019(GBD 2019). Methods The prevalence, mortality and DALY attributable to CRDs, and risk factors from 1990 to 2019 were estimated. We also assessed the driving factors and potentiality for improvement by decomposition analyses and frontier analyses. Results In 2019, 454.56 (95% uncertainty interval(UI): 417.35-499.14) million individuals worldwide had a CRD, showing a 39·8% increase compared with 1990. Deaths due to CRDs numbered 3.97(95%UI: 3.58-4.30) million, and DALY in 2019 was 103.53 (95%UI:94.79-112.27) million. Declines by average annual percent change(AAPC) were observed in age-standardized prevalence rates(ASPR) (0.64% decrease), age-standardized mortality rates(ASMR) (1.92%), and age-standardized DALY rates(ASDR) (1.72%) globally and in 5 socio-demographic index (SDI) regions. Decomposition analyses represented that the increase in overall CRDs DALY was driven by aging and population growth. Chronic obstructive pulmonary disease (COPD) was the leading driver globally. Frontier analyses witnessed significant improvement opportunities at all levels of the development spectrum. Smoking remained a leading risk factor(RF) for the mortality and DALY, although, it showed a downward trend. Air pollution, a growing factor especially in relatively low SDI regions, deserves our attention. Conclusion Our study clarified that CRDs remain a leading cause of prevalence, mortality and DALY worldwide, with growth in absolute numbers but declines in several age-standardized estimators since 1990. The estimated contribution of risk factors to mortality and DALY supports the need for urgent measures to improve them.